Jinx’s Character Development Shapes Irony in Christian Linke’s Arcane Season One (2021) - Fadilah, Nizam; Nurholis, Nurholis; Sudarisman, Yoga (Journal of English Language and Education, 2025)
Character development is a literary element that refers to the process through which characters are shaped with traits that establish their role and presence within the narrative world. This research aims to analyze the character development of Jinx in Arcane Season one (2021) using film theories by Petrie Boggs, with a particular focus on identifying the irony that shapes. A descriptive qualitative approach is used due to the use of narrative structure, visuals, and dialogue. The study identifies six key moments in Jinx’s development across episodes 1 to 9. Each moment is marked by a specific type of irony: dramatic irony, irony of situation, irony of character, irony of setting, irony of tone, and cosmic irony. This irony serves to deepen the audience’s understanding of her complex identity shift from Powder to Jinx. This study concludes that Arcane constructs Jinx’s character development as an ironic tragedy. Each ironic turn in the story underscores the tension between who Jinx was, how others perceived her, and who she chooses to become.